Systems implantation: a comparative study and identification of gaps in usual methodologies - Panizzi, Marisa D. (2017)
Systems implantation is one the phases of the software process where the human interaction dimension becomes relevant. However, weakness in the supervision of this dimension is a factor that in many cases leads to the failure of the Project. In this work, systematization and control of the implantation activities in the following methodologies is reported: IEEE 1074, Métrica V3, Rational Unified Process, and SCRUM. An instrument for their comparison is proposed, including the rationale for the analytical dimensions used, and a preliminary interpretation of results is presented emphasizing gaps.